OA-PICA bypass for the treatment of aneurysm of vertebral artery and PICA using çLé shape incision and multiple-layer dissection of suboccipital muscles - อัครธรรมโชติ, นาแสง; ศรีอมรรัตนกุล, กิติพร (Thai Journal of Neurological Surgery, 2025)
This article describes the surgical techniques of occipital artery- posterior inferior cerebellar artery (OA-PICA) bypass for treatment of 7 patients with vertebral artery and PICA aneurysm using "L" shape skin incision and multiple-layer dissection of suboccipital muscle techniques. There were 6 patients with vertebral artery dissecting aneurysm, and 1 patient with proximal PICA aneurysm. The postoperative patency rate of bypass graft and complete obliteration rate of aneurysm were 100%. Two patients (28.6%) had surgical complication, 1 patient had surgical wound infection and 1 patient had postoperative diaparesis and dysphagia. The presented techniques are safe and provide high patency rate of bypass graft.